Geospatial mapping of an Orang Asli (Indigenous People) settlement using a UAV and GIS approach - Nur Hakimah Asnawi,; Abdul Aziz Ab Rahman,; Rokiah Omar, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The utilisation of Unmanned Aerial Vehicles (UAV) has become ubiquitous in multidiscipline because of its advanced capabilities and multifunctional. This device can be very useful especially in remote and distant locations such as Orang Asli settlements to determine the geographical characteristics and land-use area for prospective community engagement and development programmes. This study aimed to use a UAV integrated with a Geographic Information System (GIS) to produce a land-use map of a distant rural indigenous community with accurate geospatial data. Aerial photography was captured using a UAV during a field trip to the Pos Gob Orang Asli Settlement, Gua Musang District in October 2019. UAV aerial photography was used to capture high-resolution images of the settlement as it is located deep in the tropical jungle along the Central Spine (Banjaran Titiwangsa) in Kelantan. The aerial photographs captured were analysed using Agisoft Photoscan i.e. photogrammetric digital processing software to produce an orthophoto. The orthophoto was then processed in GIS application for visual interpretation through the digitalisation of the captured geographical features and various socio-cultural developments found in the settlement to generate a land-use map. The digitized land-use features were classified into housing, commercial, institutional, public facilities, infrastructure, utilities, green space/forest, water bodies, and off-road types. Geospatial mapping of remote rural settlements using a UAV and GIS application is an alternative method in acquiring updated land-use patterns instantly. This UAV method has advantage with greater cost-effectiveness in data acquisition especially when funding and manpower is limited. In conclusion, the use of UAV with GIS approach provides a precise method of determining site land area and to produce an updated land use map that can be used for monitoring development planning and implementation of community projects.